2015
DOI: 10.1086/680400
|View full text |Cite
|
Sign up to set email alerts
|

The invasive Asian clam (Corbicula fluminea) increases sediment denitrification and ammonium flux in 2 streams in the midwestern USA

Abstract: The invasive Asian clam, Corbicula fluminea, can enhance conditions needed for denitrification, but the effects of C. fluminea on denitrification in streams have not been measured. In summer 2012, we incubated sandand gravel-filled boxes in the North Branch of the Chicago River, Illinois (high nutrient), and Eagle Creek, Michigan, USA (low nutrient). One side of the box contained no clams (control), and the other contained C. fluminea. After 6 wk in situ, we measured inorganic N and dissolved-gas fluxes using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…When the correlation between environmental factors and C. fluminea and U. delphinus densities were analysed, only the ammonium and phosphate concentrations in the water column were found to be significant and positively correlated with each species, respectively. Turek and Hoellein () suggested that C. fluminea increased nitrogen flux via direct excretion or mineralization of clam wastes. Vaughn, Gido, and Spooner () related nutrient excretion (including phosphorus) to overall freshwater mussel biomass.…”
Section: Discussionmentioning
confidence: 99%
“…When the correlation between environmental factors and C. fluminea and U. delphinus densities were analysed, only the ammonium and phosphate concentrations in the water column were found to be significant and positively correlated with each species, respectively. Turek and Hoellein () suggested that C. fluminea increased nitrogen flux via direct excretion or mineralization of clam wastes. Vaughn, Gido, and Spooner () related nutrient excretion (including phosphorus) to overall freshwater mussel biomass.…”
Section: Discussionmentioning
confidence: 99%
“…One of the more common MIMS methods used to estimate denitrification is the continuous-flow core method. The continuous-flow core method originated in estuarine sediments [Kana et al, 1998;An et al, 2001;Gardner and McCarthy, 2009] but has since been applied in freshwater ecosystems [Bernot et al, 2003;Smith et al, 2006;Turek and Hoellein, 2015]. Continuous-flow cores overcome some of the major limitations for estimating denitrification [Groffman et al, 2006] by using intact sediment cores with natural substrate availability and no chemical inhibitors.…”
Section: Partitioning Water Column and Sediment Processesmentioning
confidence: 99%
“…Technological developments have facilitated several denitrification estimates using dissolved N 2 measurements made with membrane-inlet mass spectrometry (MIMS) [Kana et al, 1994] for high-precision estimates of dissolved N 2 , oxygen (O 2 ), and argon (Ar). The MIMS approach has most commonly been used in estuarine studies [Kana et al, 1998;An et al, 2001;Gardner and McCarthy, 2009] but is increasingly used in freshwater ecosystems both at mesocosm [Smith et al, 2006;Fork and Heffernan, 2014;Turek and Hoellein, 2015] and reach scales [Laursen and Seitzinger, 2002;Baulch et al, 2010]. Denitrification estimates from previous reach-scale approaches [Laursen and Seitzinger, 2002;McCutchan et al, 2003;Pribyl et al, 2005] are high compared to other aquatic ecosystems, but these high rates may be due to uncertainty involved in parameters needed for reach-scale denitrification models [Baulch et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…Although clam cultivation in Cherrystone Inlet tends to favor DNRA, the overall effect of bivalves on NO3 respiration rates is quite variable and highly dependent on the environment and type of bivalve. Some studies report denitrification enhancement in bivalve‐dominated sediments compared to reference locations (Kellogg et al ; Smyth et al ; Turek and Hoellein ) while other studies show no difference in denitrification across sediment types (Christensen et al ; Jones et al ; Higgins et al ). Still other studies report spatial and/or temporal variability on the effects of bivalves on sediment denitrification (Nizzoli et al ; Carlsson et al ) and recently a study reported a decrease in denitrification in the presence of high clam abundance (Bonaglia et al 2014).…”
Section: Discussionmentioning
confidence: 99%